Sub-Saharan African immigrant women's experiences of (lack of) access to appropriate healthcare in the public health system in the Basque Country, Spain - Iratxe Pérez-Urdiales (International Journal for Equity in Health, 2019)
Abstract Background Immigrant populations face diverse barriers to accessing appropriate healthcare services on several levels. In the Basque Country, Sub-Saharan African women were identified as facing the largest barriers to access them. The aim of the study is to analyse Sub-Saharan African immigrant women's perceptions and experiences of access to appropriate healthcare in the public health system in the Basque Country, Spain. Methods Fourteen women from eight Sub-Saharan African countries who have used the Basque public healthcare services were interviewed. A qualitative content analysis was applied: meaning that units were identified, coded and the resulting codes were then organized into three categories. Results The first category, Fearing to enter a health system perceived as not friendly for immigrants, included factors, mainly those related to legal conditions for accessing healthcare services and lack of lawful documentation, that made women avoid or discontinue seeking out healthcare. The second category, Being attended on professionals' own communication terms, comprised how the lack of effective communication compromised not only the access of the immigrant women to healthcare services, but also their health. Lastly, the third category, Is mistreatment based on racism or merely on bad luck? described how being an immigrant and black influenced the way they were (mis)treated in the health system. Conclusion For Sub-Saharan African immigrant women, accessing appropriate healthcare in the Basque Country was perceived to be subject to institutional barriers. At the legal level, barriers included lack of entitlement, difficulties in fulfilling legal access conditions and lack of documentation. The lack of communication with health centre staff and their attitudes, guided by a stereotyped social image of immigrants and black people, also hindered their possibilities of receiving appropriate healthcare. Facilitators for accessing healthcare included strategies from individual professionals, personal networks and social actors to help them to cope with the barriers. There is a need of reinforcing inclusion values and rights-based approach to attention among staff at the health centres to have more non-discriminatory and culturally appropriate health systems.